Effects of the early phase of the COVID-19 pandemic on natural and ART-mediated birth rates in Lombardy Region, Northern Italy. Issue 4 (October 2021) - Somigliana, Edgardo; Esposito, Giovanna; Viganò, Paola; Franchi, Matteo; Corrao, Giovanni; Parazzini, Fabio
Abstract: Research question: What effects did the early phase of the COVID-19 pandemic have on natural and assisted reproductive technology (ART)-mediated birth rates? Design: Regional registries were consulted with permission from the Health Authorities of Lombardy Region, Northern Italy, an area particularly affected by the early phase of the epidemic. Deliveries occurring in the area between 1 January 2019 and 31 December 2020 from women beneficiaries of the National Health System and resident in Lombardy were identified. Comparisons mainly focused on December 2020, when women who conceived after 8 March (the start of the stringent lockdown imposed by the authorities) were expected to deliver. Results: When comparing the periods January to November in 2019 and 2020, a 5.1% reduction of monthly general birth rate (from 5732 in 2019 to 5438 in 2020) was observed. The contribution of ART births was similar in 2019 and 2020, being 4.4% and 4.5%, respectively. In December 2020, a notable drop in natural (–17.8%), ART-mediated (–86.6%) and overall (–21.0%) births was observed compared with December 2019. After adjusting for the expected 5.1% reduction, the inferred effect of the COVID-19 crisis corresponded to a 16.7% reduction in birth rate, of which 76% was related to natural (707 births) and 24% to ART (218 births) conceptions. Conclusions: This is the first study providing population-based evidence on the effects of COVID-19 and its related stringent restrictions on birth rates. The birth rate was dramatically reduced following the critical period, and the closure of ART centres played only a marginal role (24%) in the overall detrimental effect.